Polityka zagraniczna i bezpieczeństwo w programach wyborczych partii politycznych podczas kampanii parlamentarnej 2019 r. w Ukrainie: Foreign and security policy in the election programs of political parties during the 2019 parliamentary campaign in Ukraine - Pietnoczka, Paweł (Przegląd Wschodnioeuropejski, 2021)
The aim of the article is to present programme priorities concerning the foreign and security policy as proclaimed by political parties during the parliamentary campaign in 2019 in Ukraine. It shows how the parties intended to ensure state security, bring peace to Donbass, restore territorial integrity, and which countries and international organisations they saw as the main allies of Ukraine on the way to achieving these objectives. The election programs of individual political parties were analysed, with the focus on the postulates of those parties which received at least three percent of the support in the election, i.e. Servant of the People, Opposition Platform – For Life, Fatherland, European Solidarity, Voice, Radical Party of Oleh Lyashko, Strength and Honor and Opposition Bloc.